The Fusion of International and Domestic Law in a Globalised World - Aksamitowska, Karolina (Utrecht Journal of International and European Law, 2017)
Keywords: death penalty; capital cases; discrimination litigation; standard of proof; fair trial and equality protection; postconflict justice and transition; Islamic law; Shari’a; international humanitarian law; international human rights law; extremism, political violence, Islamism; freedom of expression; terrorism, extremism, counter-terrorism, counter-extremism; Article 19 International Covenant on Civil and Political Rights; Abuse of rights; Directive 2004/38; Court of Justice of the European Union; Marshall Islands Cases; ICJ; Electronic waste; sustainable development; WTO, GATT, TBT Agreement